2022
DOI: 10.1097/ncc.0000000000001139
|View full text |Cite
|
Sign up to set email alerts
|

Oncology Outpatients With Worse Anxiety and Sleep Disturbance Profiles Are at Increased Risk for a Higher Symptom Burden and Poorer Quality of Life

Abstract: Background Anxiety and sleep disturbance are frequent symptoms during chemotherapy. Objectives Purposes were to identify subgroups of oncology outpatients with distinct joint anxiety and sleep disturbance profiles, as well as evaluate for differences in demographic and clinical characteristics, sleep disturbance characteristics, severity of common symptoms, and quality-of-life outcomes among these subgroups. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 88 publications
(177 reference statements)
0
6
0
Order By: Relevance
“…Today, the rate of breast cancer survivors is high, due to advances in early diagnosis and treatment. Efforts to improve the quality of life of these individuals, who have many needs, are of critical importance in nursing care practice 30,31 . Chemotherapy is an important component of cancer treatment 32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Today, the rate of breast cancer survivors is high, due to advances in early diagnosis and treatment. Efforts to improve the quality of life of these individuals, who have many needs, are of critical importance in nursing care practice 30,31 . Chemotherapy is an important component of cancer treatment 32 .…”
Section: Discussionmentioning
confidence: 99%
“…to improve the quality of life of these individuals, who have many needs, are of critical importance in nursing care practice. 30,31 Chemotherapy is an important component of cancer treatment. 32 At the same time, the common adverse effects of chemotherapy in cancer patients may have led to its frequent use by authors (https://www.cdc.gov/cancer/preventinfections/providers.htm).…”
Section: Kaya and Tuzcumentioning
confidence: 99%
See 1 more Smart Citation
“…Equally important, in both cross-sectional and longitudinal studies of oncology patients, positive associations were identified between sleep disturbance and fatigue [11][12][13], depression [12,[14][15][16], and anxiety [6,[17][18][19][20]. In a longitudinal study that evaluated for changes in the cooccurrence of sleep disturbance and fatigue in women undergoing chemotherapy for breast cancer using latent profile analysis (LPA) [21], three groups of patients were identified prior to the initiation of chemotherapy (i.e., Fatigued with Sleep Complaints, Average, Minimal 2 Symptoms).…”
Section: VImentioning
confidence: 99%
“…It typically presents in the form of “clusters” of symptoms, including pain, anxiety, depression, fatigue, and decreased morning energy ( 4 , 5 ). The severity of this syndrome is positively correlated with cognitive dysfunction, quality of life, cancer survival, and disease burden ( 6 8 ) and, if it does not achieve long-term remission, can cause insomnia ( 9 ), complicating the management of sleep-wake disorders in oncology ( 5 ). The study concluded that: sleep-wake disorders in cancer patients may be independent of the time of diagnosis of the disease and the location of the tumor, but independently related to their quality of life ( 10 ).…”
Section: Introductionmentioning
confidence: 99%